2014
DOI: 10.1002/bip.22499
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations demonstrate the regulation of DNA‐DNA attraction by H4 histone tail acetylations and mutations

Abstract: The positively charged N-terminal histone tails play a crucial role in chromatin compaction and are important modulators of DNA transcription, recombination, and repair. The detailed mechanism of the interaction of histone tails with DNA remains elusive. To model the unspecific interaction of histone tails with DNA, all-atom molecular dynamics (MD) simulations were carried out for systems of four DNA 22-mers in the presence of 20 or 16 short fragments of the H4 histone tail (variations of the 16-23 a. a. KRHRK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 89 publications
(149 reference statements)
5
25
0
Order By: Relevance
“…More recently, Collepardo-Guevara et al in a multiscale simulations showed that lysine acetylation increased secondary-structure content within the histone tail and decreased tail availability for crucial fiber compacting internucleosome interactions [54], consistent with earlier simulations of conformational ensemble of fragments of histone tails without DNA in solution [55, 56]. These results are also in line with the previous simulations of DNA interactions with H4-tail peptides [57, 58], which suggested that charged groups of arginines and lysines play major roles in the tail-mediated DNA-DNA attraction by forming bridges with phosphates and interacting with electronegative sites in the minor groove.…”
Section: Resultssupporting
confidence: 86%
“…More recently, Collepardo-Guevara et al in a multiscale simulations showed that lysine acetylation increased secondary-structure content within the histone tail and decreased tail availability for crucial fiber compacting internucleosome interactions [54], consistent with earlier simulations of conformational ensemble of fragments of histone tails without DNA in solution [55, 56]. These results are also in line with the previous simulations of DNA interactions with H4-tail peptides [57, 58], which suggested that charged groups of arginines and lysines play major roles in the tail-mediated DNA-DNA attraction by forming bridges with phosphates and interacting with electronegative sites in the minor groove.…”
Section: Resultssupporting
confidence: 86%
“…Simulations were run for 40 ns collecting atom coordinates with 1 ps resolution. Detailed description of the simulations and major results are reported in our earlier work [76].…”
Section: Atomistic Molecular Dynamics Simulationsmentioning
confidence: 99%
“…12 ) provide detailed views, as well as mechanistic and thermodynamic information, complementing experiments that might lack the spatial resolution to provide a molecular perspective of the problem. Hardware and software advances have allowed several all-atom sim-ulations of isolated histone tails 13 , tails with DNA 13a, 14 , and even nucleosomes 15 with explicit solvent and ions. All-atom molecular dynamics (MD) simulations in both implicit 16 and explicit solvent 13b suggested that the histone tail peptides are not fully disordered.…”
mentioning
confidence: 99%